REGULARIZAÇÃO FUNDIÁRIA NO BRASIL CONTEMPORÂNEO: para além da interpretação jurídica - Celso Severo da Silva (Universidade Federal do Maranhão, 2018)
The present article aims to analyze how land regularization in Brazil is expressed in contemporaneity, its contradictions and interpretations. At the same time, insert its analysis in the present historical, political and economic conditions of the capitalist crisis, the role of the State and the materialization ofthe use and occupation of the urban space. That way, the capitalist logic inserts the urban and the cities as places of reproduction. Thus, the analysis of land regularization, coupled with purely legal discussion, limits the understanding that housing, private property, and land capital are not connected with the class conflicts characteristic of class society.